2017
DOI: 10.3390/rs9070706
|View full text |Cite
|
Sign up to set email alerts
|

Dry Season Evapotranspiration Dynamics over Human-Impacted Landscapes in the Southern Amazon Using the Landsat-Based METRIC Model

Abstract: Abstract:Although seasonal and temporal variations in evapotranspiration (ET) in Amazonia have been studied based upon flux-tower data and coarse resolution satellite-based models, ET dynamics over human-impacted landscapes are highly uncertain in this region. In this study, we estimate ET rates from critical land cover types over highly fragmented landscapes in the southern Amazon and characterize the ET dynamics during the dry season using the METRIC (Mapping Evapotranspiration at high Resolution with Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 42 publications
2
20
0
2
Order By: Relevance
“…On the other hand, results indicate that the SEBAL slightly overestimated daily ET when compared to eddy covariance measurements, which is in accordance with other studies [51,55,61,[95][96][97], with errors ranging between 0.3-0.4 mm day −1 when compared to measurements forced by energy balance closure techniques, and 0.6-0.8 mm day −1 when compared to measurements without energy balance closure. A better performance of the SEBAL at a daily time scale is possibly related to the small fraction of G and ∆S on a daily time scale [92,94], closely relying on the accurate estimates of Λ and R n 24h .…”
Section: Uncertainties In the Sebal Instantaneous And Daily Et Estimatessupporting
confidence: 91%
“…On the other hand, results indicate that the SEBAL slightly overestimated daily ET when compared to eddy covariance measurements, which is in accordance with other studies [51,55,61,[95][96][97], with errors ranging between 0.3-0.4 mm day −1 when compared to measurements forced by energy balance closure techniques, and 0.6-0.8 mm day −1 when compared to measurements without energy balance closure. A better performance of the SEBAL at a daily time scale is possibly related to the small fraction of G and ∆S on a daily time scale [92,94], closely relying on the accurate estimates of Λ and R n 24h .…”
Section: Uncertainties In the Sebal Instantaneous And Daily Et Estimatessupporting
confidence: 91%
“…Studies using this approach have been developed in the Amazon region, but most of them make use of satellite data with medium and low spatial resolution (30 m to 1 km; de Oliveira et al, 2016;de Oliveira et al, 2017;de Oliveira & Moraes, 2013;Khand, Numata, Kjaersgaard, & Vourlitis, 2017;Numata, Khand, Kjaersgaard, Cochrane, & Silva, 2017;Santos, Nascimento, Rao, & Manzi, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The NDVI in 1985 showed that the microbasin was covered by forests due to darker shades, and the NDVI values of 0.60 are common in regions of tropical rainforest 22,23 . Negative NDVI values in 2000 and 2015 show reduced native vegetation with soil exposure and watercourses.…”
Section: Discussionmentioning
confidence: 99%